Legal Protection of Unregistered Foreign Trademarks in Indonesia - Dhia Savitri Dewantari; Rahmi Jened (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2026)
This study aims to analyze legal protection for trademarks in Indonesia and the available recovery measures for owners of foreign marks that are not yet registered in Indonesia when similar marks are registered by other parties in bad faith. The research method used is normative juridical legal research employing a statutory approach, conceptual approach, and case study approach, with the dispute over the ARC’TERYX mark as the main case. The novelty of this research lies in its focused formulation of practical legal strategies for unregistered foreign trademark owners facing registrations by third parties, by mapping the relevant legal bases under Indonesian Trademark Law and translating them into step-by-step recovery options (registration plus litigation) specifically in the ARC’TERYX dispute context. The results show: (1) Trademark protection in Indonesia follows the territorial principle and a constitutive registration system, where rights are generally granted to the first registrant acting in good faith. Exclusive trademark rights encompass economic and moral dimensions, including the right to use, license, and transfer trademark rights. Protection is limited for marks that conflict with morality, religion, and decency, and for marks consisting of generic terms. Violations can be direct or indirect, with remedies through civil claims, criminal proceedings, and alternative dispute resolution. (2) For the ARC’TERYX (Canada) owner, recovery may be pursued by registering the mark in Indonesia and simultaneously filing a civil lawsuit to cancel the registration IDM000731218 ARCTERYX (China) on relative grounds of bad faith under Article 76(1)(2) in conjunction with Article 21(3) of Law No. 20 of 2016. Alternatively, cancellation may be sought based on infringement of a well-known mark under Article 76(1)(2) in conjunction with Article 21(1)(b) and (c) of Law No. 20 of 2016.